Protecting the Right to Privacy in China - Jingchun, Cao (Victoria University of Wellington Law Review, 2005)
This article suggests the Chinese government should establish systematic legal protection for personal privacy in China. First, a brief introduction to the history of the concept of privacy in China is given. Based on the definition of privacy in the Western world, the modern concept of privacy has been absorbed by Chinese scholars and defined according to Chinese norms. During this process, the subjects and objects of the right to privacy have been chosen and the distinctions between the right to privacy, the right of reputation and the right to know have been made clear. This article considers that it is most important to recognise the right to privacy as an independent right both in the Constitution and Civil Code. Depending on the impact of the breach of privacy, liability for civil or criminal punishment should attach. Besides these measures, a specific data protection law is also essential.